2013
DOI: 10.1007/s12262-012-0794-z
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Wall Synovial Sarcoma During Pregnancy—a Case Report

Abstract: Synovial sarcoma is rare, aggressive, malignant mesenchymal neoplasm. The recent literature does not validate its only prevalence in the extremities of the adult population. Statistics reveal that adult population has the highest prevalence rate; 30 % of reported cases occur in the children and adolescents. It is very rare in pregnancy. Carcinomas may be diagnosed concurrently with pregnancy in approximately 0.1 % of cases, but sarcomas are rare. We report a 21-year-old woman with synovial sarcoma on anterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
0
10
0
3
Order By: Relevance
“…dyspnea, hematuria. Most women died of advanced disease [29] , [66] , [67] , [68] , [69] , [70] , [71] , [72] .…”
Section: Literature Searchmentioning
confidence: 99%
“…dyspnea, hematuria. Most women died of advanced disease [29] , [66] , [67] , [68] , [69] , [70] , [71] , [72] .…”
Section: Literature Searchmentioning
confidence: 99%
“…Our literature search revealed that only 12 cases of synovial sarcomas during pregnancy have been reported since 2006. Of the 12 cases of synovial sarcomas during pregnancy that have been reported since 2006, five were pulmonary,3–7 three were renal,8–10 two involved the head and neck,11 12 one involved the abdominal wall,13 and the last, like our patient, involved the upper left thigh 14. The three patients who passed away during the course of follow-up all had the diagnosis of pulmonary synovial sarcomas.…”
Section: Discussionmentioning
confidence: 49%
“…1 El lugar de presentación habitual son las extremidades, sin embargo, puede localizarse en cabeza y cuello, pared abdominal, tracto gastrointestinal, corazón, riñón, peritoneo, pulmón y pleura. [4][5][6] El debut como tumor primario de pulmón y/o pleura, es raro y altamente agresivo. [7][8][9][10] Se presenta entre las edades de 15 y 40 años 11,12 con una media de edad de 38 años; no tiene diferencias en cuanto al sexo y no se relaciona con el tabaquismo.…”
Section: Discussionunclassified